2002
DOI: 10.1080/01443610120101790
|View full text |Cite
|
Sign up to set email alerts
|

Investigating non-attendance at colposcopy clinic

Abstract: We investigated non-attendance at colposcopy clinic. This was a retrospective case-control study conducted to find out any specific characteristics for women who failed to attend their appointment at colposcopy during a 3-month period, in comparison to attenders. The incidence of non-attendance was 23.7%. Younger age, smoking, occurrence of pregnancy, previous history of termination of pregnancy, anxiety and follow-up appointments were more common in non-attenders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
5
1
Order By: Relevance
“…In the literature, the default rate of colposcopy appointments varies widely, between 8% and 24%. [8][9][10][11] In this study, the default rate of initial colposcopy appointments (15.8%) was slightly higher than the NHSCSP 2004 minimum requirements (< 15%). In the United Kingdom, interventions including sending a detailed leaflet with a reminder letter regarding the appointment and pre-clinic telephone contact have proved to be practical and can effectively reduce the default rate.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In the literature, the default rate of colposcopy appointments varies widely, between 8% and 24%. [8][9][10][11] In this study, the default rate of initial colposcopy appointments (15.8%) was slightly higher than the NHSCSP 2004 minimum requirements (< 15%). In the United Kingdom, interventions including sending a detailed leaflet with a reminder letter regarding the appointment and pre-clinic telephone contact have proved to be practical and can effectively reduce the default rate.…”
Section: Discussioncontrasting
confidence: 54%
“…3 Because of numerous background differences between individual populations and types of visit, a wide variation of reported factors that influence default of colposcopy appointments is anticipated. [8][9][10] In this study, lack of health insurance, being known to have HIV infection and waiting times longer than 4 weeks of referral were significant independent predictors of missed initial colposcopy appointments. These significant predictors found at an individual setting should be taken into consideration when designing protocols for enhancing patientsÕ compliance and managing default problems.…”
Section: Discussionmentioning
confidence: 57%
“…This phenomenon was observed in previous studies [4,6,10,17] , although relatively low nonattendance rates (16%) were reported in an adolescent women's health clinic [13] . It is suggested that the lower proportion of nonattendance in older age reflects poorer health and therefore increased motivation to seek assistance from a physician.…”
Section: Discussionmentioning
confidence: 61%
“…Our study was also unable to analyse failed appointments by clinical condition and symptoms. Other studies have shown that different clinical conditions and health status may be linked to failed attendances [23,24]. Future studies should include such variables to increase the predictive accuracy, but we note that our methodology already has diagnostic accuracy of more than 80% on the basis of routinely available data alone.…”
Section: Discussionmentioning
confidence: 89%